ANALYSIS OF THE EFFECT OF KNOWLEDGE MANAGEMENT, COMPETENCY, AND INNOVATION ON EMPLOYEE PERFORMANCE - Wibowo, Dwi Yoga Ari; Muljono, Pudji; Sumertajaya, I Made (Jurnal Aplikasi Manajemen, 2021)
The conformity of employee competencies with their positions and innovation in work implementation is required by the presence of the Civil Servants (PNS) professional demands. Knowledge management is necessary to fulfill the knowledge needs of employees so that competence, innovation, and employee performance can be improved. This study aims to analyze the effect of knowledge management, competence, and innovation on employee performance. All employees in the Finance and Equipment Bureau of the Ministry of Agriculture were involved as the research object. The data were obtained using the census method of 103 Finance and Equipment Bureau employees, interviews with appraisal officials and personnel managers, and employee performance appraisals in 2019. The data processing uses Structural Equation Modeling - Partial Least Square (SEM PLS) analysis. This study indicates that knowledge management has a significant effect on innovation and competence, whereas innovation significantly affects performance. However, knowledge management and competence do not seem to have a significant effect on employee performance. Knowledge management indirectly has a significant effect on performance through innovation. Nevertheless, knowledge management does not seem to have a significant effect on performance through competence. The suggestion for further research is it shall be conducted in a work unit that requires special skills so that the employee competence is taken into consideration.